Affine Anosov Diffeomorphims of Affine Manifolds - Aristide Tsemo (International Journal of Mathematics and Mathematical Sciences)
We show that a compact affine manifold endowed with an affine Anosov transformation is finitely covered by a complete affine nilmanifold. This is a partial answer of a conjecture of Franks for affine manifolds.